(untitled) (Journal of Environmental Microbiology and Toxicology, 2023)
Enzyme-based assay in near-real-time biomonitoring provides high sensitivity to bioavailable contaminants, leading to quick results that support prompt action. It is essential to use this method to reduce pollution in drinking, agriculture and marine waters and protect the health of both humans and animals. This work applies a previously discovered enzyme test in biomonitoring to identify contaminants, particularly zinc, in marine water samples from the Langkawi Island, an island that harbors the UNESCO’s Geoforest Park status. We used the achromopeptidase dye binding assay, specifically designed for detecting mercury zinc at levels below one part per million, to identify trace amounts of these metal successfully. The test demonstrated a sensitive, quick, and cost-efficient monitoring method with little inhibition (<10%) during a 6-hour field trial for three consecutive days, suggesting low pollution levels and confirmed by instrumental analysis. This method allows for the prompt identification of environmental pollutants, which helps take appropriate actions and safeguard ecotourism locations by offering data-driven information for policy development. Enzyme tests are simple and visually appealing, making them effective instructional tools that help raise environmental awareness and support conservation initiatives. Our research highlights the need to use enzyme tests for broad environmental evaluation, harmonizing local monitoring methods with global standards, and promoting international cooperation in environmental conservation. This work enhances our comprehension of ecological well-being in marine and brackish waterways and underscores the significance of ongoing monitoring to protect natural environments.